The Potential Of Pumpkin (cucurbita Moschata Duschene) As Commercial Crop In Malaysia - Aimi Fadzirul, Kamarubahrin; Siti Nurazira, Mohd Daud; Asmaddy Haris; Zurina Kefeli@ Zulkefli; Nursilah Ahmad; Nurul Aini Muhamed; Syadiyah Abdul Shukor (Universiti Putra Malaysia Press, 2024)
Awareness of recommendations for fruit and vegetable consumption has increased substantially over the last 20 years. In addition, fruits and vegetables such as pumpkin (Cucurbita moschata Duchesne) are good sources of many important nutrients, including potassium, vitamin C, folate, fibre, and numerous phytochemicals. Malaysia produces pumpkin its own, with considerably large areas of production comparable to its high global demand. However, in reality, there is a limitation in the commercial production as the local pumpkin is very much dependent on the market demand as the utilization has been limited to the consumption of fresh product. Thus, the objective of the study first initiative to provide the information about the pumpkin and second to investigates the opportunities on commercialized local pumpkin in Malaysia as by products despite various nutritious it is also listed as prophetic foods. The scientific research that covered a broad range of in vitro to in vivo studies on the by-products potentials of these fruits is also discussed in detail. The current review is an update for researchers to have a better understanding of the pumpkin, which simultaneously can provide awareness to enhance their commercial value and promote their utilization. Malaysia have potential to growth pumpkin instead of continuously importing. The daily consumption of pumpkins may provide various health benefits to human. Future investigation is needed to explore the potential of pumpkin as by products in order to increase its competitiveness and self-sufficiency